Efektivitas Dakwah Melalui Media Sosial Tiktok dalam Meningkatkan Nilai-Nilai Keberagamaan - Salma Humaira Supratman; Rodliyah Khuza’I; Hendi Suhendi (UPT Publikasi Ilmiah Unisba, 2022)
Abstract- TikTok is one of the most popular social media in Indonesia. Not a few people use TikTok as a medium of propaganda, one of which is an account called @amaljariah.ku. But how is the effectiveness of @amaljariah.ku's da'wah in increasing religious values ​​that are spread through propaganda videos on TikTok social media. Based on this, the researcher conducted a study entitled The Effectiveness of Da'wah Through Tiktok Social Media in Improving Religious Values ​​(Study on Tiktok @amaljariah.ku Account). This study aims to determine the da'wah activity on the TikTok @amaljariah.ku account, the religious values ​​of the followers of the TikTok @amaljariah.ku account and the effectiveness of the preaching of the TikTok @amaljariah.ku account in increasing religious values. This research uses qualitative research methods and uses and gratification theory. Data obtained through documentation and interviews. The results obtained from this study are the effectiveness of da'wah through tiktok social media in increasing religious values ​​on the @amaljariah.ku tiktok account proven to be effective in increasing the religious values ​​of followers of the @amaljariah.ku TikTok account. Abstrak- TikTok adalah salah satu media sosial yang banyak digandrungi masyarakat Indonesia. Tidak sedikit orang yang menggunakan TikTok sebagai media dakwah, salah satunya adalah akun bernama @amaljariah.ku. Namun bagaimana efektivitas dakwah -nilai keberagamaan yang disebarkan melalui video-video dakwah pada media sosial TikTok. Berdasarkan hal tersebut peneliti melakukan penelitian dengan judul Efektivitas Dakwah Melalui Media Sosial Tiktok dalam Meningkatkan Nilai-Nilai Keberagamaan (Studi pada Akun Tiktok @amaljariah.ku). Penelitian ini bertujuan untuk mengetahui aktivitas dakwah pada akun TikTok @amaljariah.ku, nilai-nilai keberagamaan followers akun TikTok @amaljariah.ku dan efektivitas dakwah akun TikTok @amaljariah.ku dalam meningkatkan nilai-nilai keberagamaan. Penelitian ini menggunakan metode penelitian kualitatif dan teori uses and gratification. Data diperoleh melalui dokumentasi dan wawancara. Hasil yang didapatkan dari penelitian ini adalah efektivitas dakwah melalui media sosial tiktok dalam meningkatkan nilai-nilai keberagamaan pada akun tiktok @amaljariah.ku terbukti efektif meningkatkan nilai-nilai keberagamaan followers akun TikTok @amaljariah.ku.